2015
DOI: 10.1177/0046958015573494
|View full text |Cite
|
Sign up to set email alerts
|

A Cost Analysis of Kidney Replacement Therapy Options in Palestine

Abstract: This study provides a cost analysis of kidney replacement therapy options in Palestine. It informs evidence-based resource allocation decisions for government-funded kidney disease services where transplant donors are limited, and some of the common modalities, i.e., peritoneal dialysis (PD) and home hemodialysis (HD), are not widely available due to shortages of qualified staff, specialists, and centers to follow the patient cases, provide training, make home visits, or provide educational programs for patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Patients who reach ESRD stage will need renal replacement therapy (RRT) either through kidney transplantation or maintenance dialysis (Abecassis et al 2008;Kaza et al 2015). In the West Bank in Palestine, a dramatic increase in the numbers of ESRD patients was observed over the last few years (Younis et al 2015). In 2015, 1224 patients in the West Bank were documented to have ESRD and required hemodialysis (HD), revealing an increase of > 80% compared to 2011 (Ministry of Health, Palestinian Health Information Center 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Patients who reach ESRD stage will need renal replacement therapy (RRT) either through kidney transplantation or maintenance dialysis (Abecassis et al 2008;Kaza et al 2015). In the West Bank in Palestine, a dramatic increase in the numbers of ESRD patients was observed over the last few years (Younis et al 2015). In 2015, 1224 patients in the West Bank were documented to have ESRD and required hemodialysis (HD), revealing an increase of > 80% compared to 2011 (Ministry of Health, Palestinian Health Information Center 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The study found that the total cost per HD patient during visits to dialysis centres was an average of US$16085 per year which covered all medications, laboratory tests, and outpatient visits. The Palestinian government covered almost all of the costs of HD and transplantation [24].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the rst-year cost (16 277 USD) of kidney transplantation was fully offset in just 1.24 years by the yearly cost savings of 13 125 USD (16 085 USD for dialysis minus 2960 USD for kidney transplantation. [8] Some similar studies on cost-effectiveness between kidney transplantation and hemodialysis have been conducted. A study by Sanchez-Escuredo et al was done in 2014 with the use of prospective descriptive study.…”
Section: Discussionmentioning
confidence: 99%